DEVELOPING FOR TRANSIT TRANSPORT IN UZBEKISTAN (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the development of transit transport in Uzbekistan, focusing on its strategic location and potential as a regional transport hub. The paper analyzes current infrastructure projects, including road, rail, and logistics networks, and evaluates government initiatives aimed at improving connectivity and trade flow. Emphasis is placed on international cooperation, investment opportunities, and the role of transit transport in boosting economic growth. The study also highlights existing challenges such as regulatory barriers and infrastructure modernization. Recommendations are made to enhance efficiency, regional integration, and Uzbekistan's position in global transit corridors.